Fungi as deterioration agents of historic glass plate negatives of Brandys family collection. (November 2016) - Kwiatkowska, Magdalena; Ważny, Rafał; Turnau, Katarzyna; Wójcik, Antoni
Abstract: Microbiological deterioration was observed on a historic collection of retouched glass plate negatives. The collection came from a burnt manor house that belonged to the Brandys family before World War IInd. The photographs were taken at the end of 19th century. The collection consists of 35 glass plate negatives, 4 of which were examined for possible presence of microorganisms. The current state of the negatives indicated that the collection may have been flooded. Initially, the viability of the microorganisms on the plates was examined using luminescence adenosine phosphate assay. The fungi were isolated and identified with molecular biology methods as Trichoderma longibrachiatum, Hypocrea lixii, Aspergillus versicolor, Penicillium sp. As the historic negatives were covered with a protective varnish layer, the impact of the isolated fungi on test negative plates covered with dammar and sandarac varnishes, and on a gelatine image layer were examined. The most effective in degradation of gelatine emulsion was T. longibrachiatum. All of the investigated microorganisms quickly decomposed silver image in gelatine layer not covered with varnish in opposite to slower decomposition of silver image in gelatine layer covered with sandarac and dammar varnishes. UV-induced luminescence observation confirmed that the microorganisms quickly decomposed gelatin layer not covered with varnish. The cracking of varnish was the result of fungal activity within gelatin, however, some fungi also attacked the varnish itself. Highlights: Historic glass plate negatives of Brandys family collection were studied. Trichoderma longibrachiatum, Hypocrea lixii, Aspergillus versicolor, Penicillium sp. were isolated and identified. The fungi negatively affected plates covered with dammar, sandarac varnishes and gelatine layer. The evaluation of the effect of the isolated fungi on photographic gelatine and on photographic emulsion was carried out. T. longibrachiatum was the most effective in degradation of gelatine emulsion.